Improving die exchange process in textile manufacturing company with single minute exchange of die (SMED) - Arzmi, Muhammad Hazwan (2014)
This study presents collaboration between a textile manufacturing company in Malaysia and Universiti Teknikal Malaysia Melaka. In this Company-University Collaboration (CUC), Single Minute Exchange of Die (SMED) was introduced in the company to improve the time-consuming changeover process of its stamping machine. This project were implemented on press machine own by this company. Since this machine are currently performing critical production process, it is important that this machine could be utilized as much as it can be. The problem regarding these machine are currently changeover steps are ambiguous resulting towards a more complicated steps exist during changeover procedures. In this case it is important to identify and classify between the internal and external activities between all of them. Hence those activities later could be simplified and from that a new changeover procedure could be developed. The framework of this study involves identifying current condition of changeover procedures, identifying and separating internal and external activities, converting internal into external activities and lastly streamlining all changeover activities. Previously, the changeover time of the stamping machine in average is 5.19 hours. After the implementation of SMED, the changeover time of the stamping machine was reduced to 3.23 hours in average or (25.82%) reduction from previous changeover time. The improvements made are converting three of internal activities in to external activities. Those activities are collecting tools, collecting moulds and mould quick check. By converting these three activities into external, the changeover time could be reduced up to 11.18 minutes. As for simplifying, two of changeover activities were simplified which are mould alignment and pressure setting hence reducing time for 34.01 minutes and 49.56 minutes respectively. In conclusion, the collaboration is shown to be feasible in supporting SMED implementation in the textile manufacturing company.